Improving the Quality of Color Colonoscopy Videos. (6th February 2008) - Dahyot, Rozenn; Vilariño, Fernando; Lacey, Gerard
Abstract : Colonoscopy is currently one of the best methods to detect colorectal cancer. Nowadays, one of the widely used colonoscopes has a monochrome chipset recording successively at 60 HzR, G, andB components merged into one color video stream. Misalignments of the channels occur each time the camera moves, and this artefact impedes both online visual inspection by doctors and offline computer analysis of the image data. We propose to restore this artefact by first equalizing the color channels and then performing a robust camera motion estimation and compensation.